MEDIA PEMBELAJARAN MATEMATIKA BERBASIS KOMPUTER PADA MATERI FUNGSI - Alzuwandi; Jalinus (Prodi. Pendidikan Matematika, FKIP, Universitas Riau, 2019)
Computer technology can be utilized to create interactive learning media in the form of multimedia. Along with the development of technology need to make a computer-based learning media to help learners and teachers in learning, especially mathematics. In school, teachers use the material only from cardboard media and affixed to the blackboard, and even then not the students who hold it, so far the teacher taught mathematics only using textbooks and LKS, even though the teacher already has a computer or laptop and in the school already has facilities to support the use of media based computer that is one of them is LCD projector. One way that can be done is to create interactive learning media and interesting for learners. This study aims to develop a computer-based learning media that is valid to help students understand about functions. The research steps to be done is to analyze the syllabus, RPP and textbooks, collect the required images or animations, create paper based media designs, create media on powerpoints, create frontpage, and ask to validate by experts and practitioners. The program used for the design of computer-based products is a frontpage program, microsoft power point. Learning media validated by three experts or validators and then be revised according to validator’s advice. Learning media is packaged in the form of compact disk (CD) and user manual.